The Importance of Studying History of English Literature: With Special Reference to TSP Area: Exploring the Impact of English Literature in the TSP Area (Journal of Advances and Scholarly Researches in Allied Education, 2019)
English literature a large part of our educational system cannot be avoided and separated. Lack of reading habit and listening, limited time all only add to the problems for the students in TSP area. The importance of studying history of English literature lies in the fact that it will arise excitement, interest, the desire to learn and hear more about someone or something. Literature speaks to the students concern on social issues, lending them timeless idea the Classics containing information that is directly applicable to life understanding of human condition and deeper appreciation of modern problem. Literature will helps students to explore and analyses some of life's greatest questions giving them the skills required for deeper thought process and directions to life. Literature in itself is an artistic form of human expression. It widens our experience and deepens our impulses and sensitivities.